1990
DOI: 10.1111/j.1365-2249.1990.tb05239.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine, a plant alkaloid, inhibits the production of tumour necrosis factor-alpha (cachectin) hy human monocytes

Abstract: Human mononuclear leucocytes (MNL) or the adherent fraction (monocytes) produced tumour necrosis factor-alpha (TNF-alpha) (by ELISA) in culture when stimulated with killed Staphylococcus aureus. The bisbenzylisoquinoline alkaloid, tetrandrine inhibited the capacity of MNL and monocytes to produce TNF-alpha at a concentration range of 0.1 to 5 micrograms/ml. Tetrandrine may be potentially useful in the treatment of inflammatory diseases in which TNF-alpha plays a major role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…In vitro, TET was found to inhibit the production of nitric oxide, a critical inflammatory mediator in lipopolysaccharideactivated macrophages [30]. TET also blunted the secretion of TNF-␣ by activated monocytes [10], and various cytokine released by activated T cells [9]. TET exerted a profound inhibitory effect on T cell activation in vivo, as reported in various systems by several groups.…”
Section: Discussionmentioning
confidence: 84%
“…In vitro, TET was found to inhibit the production of nitric oxide, a critical inflammatory mediator in lipopolysaccharideactivated macrophages [30]. TET also blunted the secretion of TNF-␣ by activated monocytes [10], and various cytokine released by activated T cells [9]. TET exerted a profound inhibitory effect on T cell activation in vivo, as reported in various systems by several groups.…”
Section: Discussionmentioning
confidence: 84%
“…Stephania tetrandra S. Moore (Ferrante et al, 1990). An increasing number of studies have focused on the anti-tumour properties of Tet.…”
Section: Tetrandrine (Tet) Is a Bisbenzylisoquinoline Alkaloid Extracmentioning
confidence: 98%
“…Tetrandrine, a plant alkaloid, was reported to inhibit the production of TNF-α by monocytes (22). Previous studies demonstrated that Ginseng radix and Radix paeoniae alba in a phytopharmaceuticals that augmented monocyte and leucocyte counts in the peripheral blood (23).…”
Section: Immunopharmaceuticalmentioning
confidence: 99%